COMMODIFICATION OF WAYANG KAMASAN PAINTING AS KRIYA PRODUCT IN KAMASAN VILLAGE KLUNGKUNG BALI - Berata, I Made (International Conference on Cultural Studies; Vol 1 (2018): Proceedings International Conference on Cultural Studies, 2018)
This paper will talk about the existence of community leaders in Kamasan Klungkung Village who are majorists in Wayang painting activities in sustaining their chronicles. Painted Activity is known as "Seni Lukis Wayang Kamasan (SLWK) Series" is a traditional art, has a strong tradition of tradition and inherited from generation to generation with Schingga's painting activities still exist in the midst of the people of Kamasan Klungkung Village. In this case there has been a commodification of Wayang Kamasan Painting, impacting on changes in society and continuity. Ichih leads to mass-oriented titles of distribution, market, and consumption under the legitimacy of capitalists. Conditions of representation of community activities of wayang kamasan paintings are constructed from Atonomists are dominated by struggle in the posbut niche, by the dispocition (society) who have symbolic capital (prestige, status, and authority). Thus, analyzes permanently the ones using the critical social theory approach. In this study there was a change in the tradition which has been entrenched in the welfare of the Kamasan Village community, namely the changes that occur are. 1) there are changes in the traditional tradition of wayang kamasan painting, 2) the real lifestyle and social nature of society, and 3) the occurrence of commodification of positive presence in the continuation of wayang painting activities, namely enriching the arts that have been inhabited in Kamasan Village communities, and creating community creativity, more creative, and can improve the economic support of the community.